Effects of partial-body cryotherapy on athletic performance and sleep quality in division I collegiate basketball athletes - Kim, T.-J.; Ha, K.-H.; Park, T.-Y.; Kim, J.-H.; Lee, J.-M.; Jung, H. C. (Journal of Human Kinetics, 2025)
This study examined the effects of short-term partial-body cryotherapy (PBC) on athletic performance and sleep quality in Division I collegiate basketball athletes. A crossover, counter-balanced design was employed with twelve collegiate basketball athletes randomly assigned to five days of a post-exercise PBC condition or a control condition. Athletic performance was assessed using six standardized tests from the Korean Basketball League (KBL) Draft combine. Objective and subjective sleep quality were measured using actigraphy and three validated sleep questionnaires, respectively. The number of pull-ups performed significantly increased after the PBC condition (9.2 ± 4.59 vs. 11.9 ± 4.77 reps, p < 0.05), whereas no improvements were observed in other performance measures, including the maximum repetitions of the 75-kg bench press, sprint speed, vertical jump height, and agility. Subjective and objective sleep quality were not enhanced after the PBC condition. These findings suggest that a short-term (5-day) application of PBC has only a limited effect on athletic performance and no effect on sleep quality. Future studies with longer intervention periods are needed to better understand the effects of PBC on athletic performance and sleep quality.